Criação lexical em textos publicitários: análise de oniônimos - Antonio Jorge de Souza (2019)
The aim of this research is to verify, through the process of the stylistic lexical neology of the onionyms - proper names of industrialized brands and products - the probability of its systematization, as well as to describe some nominal constructions resulting from this process. We have, as a corpus for this research, advertising texts of national news magazines: Veja, IstoÉ and Época. We seek to understand how the stylistic nominal lexis, created in this textual genre, as for the relation between proper names and common names, satisfy, through word formation processes, the morphosyntactic and semantic rules that govern the Portuguese language. The study of onionyms indicates the possibility of teaching them at Basic Education levels and constitutes a contribution to the development of lexical competence in our mother language. The research is based on Brito (2003), Carvalhinhos (2000, 2007), Guerios (s/d), Ullmann (1997) and Zamariano (2010) regarding the functions of the sign in the onomastic and in the evolution of this field through the times; Alves (1990), Ferraz (2006), Gonçalves (2016) and Sandmann (1992, 2001) regarding the conceptualization and delimitation of the neological lexical unit and in Antunes (2003, 2012), Cardoso (2000), Carvalho (2010, 2014) and Ferraz (2007, 2008, 2010), regarding the advertising genre and the teaching of stylistic neology. The analysis of the lexis led to the creation of a taxonomy that allowed an ellaboration of a tipology of the onionyms and highlighted the fact that the structure of these lexical units is not contemplated by the traditional Grammar. All this enabled new theoretical contributions to the study of onionyms, especially when the analysis aims at its pedagogical aspects.